Augmented reality-based software (Echo-QR) for guiding the echographic probe toward the acoustic window: a pilot study - Thevenon, A.; Derache, F.; Faucoz, O.; Zuj, K.; Chaput, D.; Arbeille, P. (Frontiers in Medical Technology, 2024)
With current technology, ultrasound imaging in remote conditions such as the International Space Station is performed with vocal guidance or using a teleoperated echographcontrolled by an expert. Both methods require real-time communications between the novice operator and expert to locate the probe over the appropriate acoustic windows (AW). The current study present the development and testing of a new augmented reality software (Echo-QR) that would allow novice operators (with no medical imaging background) to correctly locate the ultrasound probe over the AW of interest without expert assistance. On the first day of the study, positions of the probe over theAWs was identified for each organ by an expert sonographer and saved in the Echo-QR software. On the second day, the novices , independently performed the ultrasound investigation using the Echo-QR software to correctly position the probe over each organ AW.Using the ECHO-QR software, novice operators found the AW in 73 of the 79 organs (92%).The 2D images acquired by the novices "2D direct image" were acceptable for medical evaluation in 41% of the cases, However, when the "direct 2D image" did not showed the entire organa 3D capture of the volume below the probe was also performed which allowed for the extraction of the appropriate 2D image "2D/3D image"for medical evaluation in 85% of the case. Therefore, in absence of real-time communication between an isolated subject and expert sonographer, the novel software (ECHO-QR) and automated 3D volume capture can be used to obtain images usable for ultrasound diagnostic.